Investigating the associations of blood lead and cadmium with smoking-related DNA methylation and mortality among U.S. adults - Yu-Wei Fang; Ching-Way Chen; Ta-Chen Su; Chikang Wang; Chien-Yu Lin (Ecotoxicology and Environmental Safety)
Purpose: Lead and cadmium have been linked to alterations in DNA methylation (DNAm) and increased mortality. However, the role of smoking-related DNAm in the link between these heavy metals and mortality remains unclear. Approach and results: We analyzed data from 2110 participants aged 50 and older from the 1999–2002 National Health and Nutrition Examination Survey (NHANES), linked to mortality data from the National Center for Health Statistics (NCHS) with follow-up through 2019. Our study examined the associations between blood lead and cadmium levels, DNA methylation-predicted pack years of smoking (DNAmPackYrs), and mortality outcomes. Our analysis found that higher natural logarithm (Ln)-transformed lead and cadmium levels were positively associated with ln-DNAmPackYrs, with a percent change of 11.34 % (P = 0.001) for lead and 35.57 % (P < 0.001) for cadmium. Participants with both heavy metals above the 50th percentile had the highest DNAmPackYrs, with P for trend < 0.001. Weighted Cox regression analysis demonstrated both ln-lead and ln-DNAmPackYrs were linked to an elevated risk of all mortality outcomes, while ln-cadmium specifically predicted all-cause mortality. A significant interaction between lead and cadmium in relation to all-cause mortality was observed (P for interaction = 0.036). Additionally, significant interactions between DNAmPackYrs and both heavy metals were found in relation to all-cause mortality (P for interaction = 0.001 for lead; P for interaction = 0.013 for cadmium). Conclusions: Drawing from a nationally representative cohort of older U.S. adults, this study provides robust evidence linking blood lead and cadmium levels to smoking-related DNAm and increased mortality risk. Moreover, the analysis revealed additive effects of these metals on smoking-related DNAm, as well as synergistic impacts on all-cause mortality. Additionally, smoking-induced DNAm may play a role in mediating the connection between heavy metal exposure and mortality risk. Additional research is required to investigate the underlying mechanisms of these associations.